Finding functionality: Rasch analysis of the Functionality Appreciation Scale in community-dwelling adults in the US - Feng, Sarah; McDaniel, Sydney; Van de Winckel, Ann (Frontiers in Rehabilitation Sciences, 2023)
The Functionality Appreciation Scale (FAS) measures an individual's appreciation for the functions their body can perform, regardless of the individual's physical limitations. Prior studies reported on internal consistency, test-retest reliability, convergent validity, and exploratory or confirmatory factor analyses, but Rasch analysis has not yet been performed to evaluate the structural validity of the FAS.We recruited community-dwelling adults at the Minnesota State Fair and through contact lists of participants identifying interest in research done in the Brain Body Mind Lab (University of Minnesota). Community-dwelling adults with spinal cord injury (SCI) completed the FAS over Zoom. We analyzed the FAS using Rasch Measurement Theory, which produced the following outputs: item, and person fit, targeting, unidimensionality, person separation reliability (PSR), local item dependence (LID), principal component analysis of residuals (PCAR), and differential item functioning (DIF).We recruited 567 participants (average age 52.15 ± 17.5 years, 63.84% women), among which 14 adults with SCI. After rescoring 3 items and deleting 1 item, the FAS had good person and item fit (except item 4). The PCAR and subsequent paired t-tests (3.53%) confirmed the unidimensionality of the scale. There was no DIF and only one item pair had LID (item 5-6). PSR was 0.75, reflecting a capacity to differentiate groups of people with high or low functionality appreciation levels. However, there was a significant ceiling effect (28.04%) and the person mean location was 3.06±2.07 logits, indicating the FAS is too easy for community-dwelling adults in the US.Discussion: The 6-item Rasch-based FAS demonstrated unidimensionality, good item fit (except item 4) and person fit, but the FAS will require more difficult items to be added to improve the targeting of the scale, and better reliability.